Studying illicit substance exposure among urban adolescents using forensic science - Michael J Merten; Joseph G Gryzwacz; Jarrad R Wagner; Amanda L Terrell; Tia C Claybrook; Jennifer N Becnel (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2023)
There are critical challenges to measuring substance use exposure, particularly among adolescents, with major limitations to the most common methods of assessment - self-report and biomarker (urine, saliva) analysis. This study examines the use of wipe sampling as a measure of adolescent illicit substance exposure. Among low-income families, this study compared forensically analyzed wipe samples from 51 adolescents' homes and cell phones with self-reported substance use to identify overlaps and discrepancies. There were major gaps between adolescents reporting any substance use in the past year and adolescents whose homes and/or cell phones tested positive for illicit substances via wipe sample analysis. This study builds upon previous adolescent substance use and exposure research, highlighting the profound limitations of self-reported use, and introducing wipe sampling as an effective measure of toxicant exposure. Wipe samples also provide a means to examine environmental contexts in new novel ways.